Teaching Arabic through Modern Methodology: An Experimental Study: An Innovative Approach to Teaching Arabic in Tamilnadu (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The significance of teaching the Arabic language cannot be underestimated as there are about 315 million speakers of Arabic across the world. It is the official language of over 26 countries and one of the official languages of the United Nations. People around the world revere Arabic and consider it as sacred since it is the language of the Holy Quran. It is a language of religion and science and it has been taught across the globe from religious schools to Western universities.In India, there are many universities and colleges where the Arabic language is taught. But the methodology of teaching differs from one institution to another. In the last two decades, there have been several studies in developing suitable ways for teaching Arabic to non-Arabs and it is found that most schools and universities in various states of India still adhere to the old teaching methods.In Tamilnadu, teaching Arabic has taken a new dimension due to the emergence of some modern Arabic Colleges. In this regard, Bukhari Aalim Arabic College located in Chennai plays a vital role in teaching and developing communication skills in Arabic in an innovative way. The main focus of this research is to examine the curriculum, syllabus and Communicative Language Teaching Approach (CLT) adopted in this college and evaluate the successful implementation of the same to enable the students to excel in reading, writing and speaking in Arabic.